Maintaining social work connections during lockdown - MacAulay, Anne (Aotearoa New Zealand Social Work, 2021)
On Saturday 21 March 2020, Prime Minister Jacinda Ardern announced a 4-level alert system around the rise of covid-19 coronavirus in Aotearoa New Zealand. At that time there were 52 confirmed cases in New Zealand. On Monday 23 March, Ardern announced New Zealand would move to Level 4 and full lockdowni at midnight on Wednesday 25 March. Full lockdown in New Zealand meant exactly that. Everyone working from home, unless they were deemed essential workers. Retail outlets all closed. No travel unless essential. No interactions with people outside of your household—your “bubble”. In my role as Continuing Professional Development Coordinator, I connect with social workers regularly by way of webinars. We have begun using Zoom to hold discussions and consultations. I decided to set up a Zoom meeting for social workers to talk about what was happening in their workplaces, what their colleagues were talking about, how they were adapting their work.